Phonon ballistic transport in the atomic chains with different interface connections to the heat reservoir - Ye, En-Jia (2013)
Phonon transport in the uniform, dimer, Fibonacci and random atomic chains has been comparatively examined using the nonequilibrium atomistic Green's function method, with particular focus on the interface effects. The tapered and the flat contact to the heat reservoir are compared. It is found that the thermal conductance of the atomic chain depends on both the order degree of the atomic chain structure and the interface configuration. The flat contact is found to favor phonon transmission between the reservoirs and the effect depends on the atomic chain structure as well.